The effect of silver or gallium doped titanium against the multidrug resistant Acinetobacter baumannii. (February 2016) - Cochis, A.; Azzimonti, B.; Della Valle, C.; De Giglio, E.; Bloise, N.; Visai, L.; Cometa, S.; Rimondini, L.; Chiesa, R.
Abstract: Implant-related infection of biomaterials is one of the main causes of arthroplasty and osteosynthesis failure. Bacteria, such as the rapidly-emerging Multi Drug Resistant (MDR) pathogen Acinetobacter Baumannii, initiate the infection by adhering to biomaterials and forming a biofilm. Since the implant surface plays a crucial role in early bacterial adhesion phases, titanium was electrochemically modified by an Anodic Spark Deposition (ASD) treatment, developed previously and thought to provide osseo-integrative properties. In this study, the treatment was modified to insert gallium or silver onto the titanium surface, to provide antibacterial properties. The material was characterized morphologically, chemically, and mechanically; biological properties were investigated by direct cytocompatibility assay, Alkaline Phosphatase (ALP) activity, Scanning Electron Microscopy (SEM), and Immunofluorescent (IF) analysis; antibacterial activity was determined by counting Colony Forming Units, and viability assay. The various ASD-treated surfaces showed similar morphology, micrometric pore size, and uniform pore distribution. Of the treatments studied, gallium-doped specimens showed the best ALP synthesis and antibacterial properties. This study demonstrates the possibility of successfully doping the surface of titanium with gallium or silver, using the ASD technique; this approach can provide antibacterial properties and maintain high osseo-integrative potential.